Super-flat glazed ceramic rock plate and preparation method thereof

By controlling the particle size and shape of the dry particles in the glaze layer of the ceramic rock slab and the range of the initial melting point, the problems of uneven glaze surface and insufficient wear resistance of the ceramic rock slab are solved, and ultra-flat glaze surface and high wear resistance are achieved, which improves the decorative effect and service life of the product.

CN119528610APending Publication Date: 2025-02-28FOSHAN OCEANO CERAMICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411592140.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

It is difficult to obtain the effect of ultra-flat glaze during the preparation process of existing ceramic rock slabs. The glaze is prone to defects such as corrugation and uneven concave concave convexity, which affects the appearance quality and decorative effect. At the same time, there are limitations in wear resistance and corrosion resistance.

Method used

By controlling the particle size distribution and shape of dry particles in the isolation glaze layer and the surface glaze layer, spherical dry particles and irregular dry particles of different particle sizes are used to control their initial melting point range, and the initial melting point of irregular dry particles is lower than the initial melting point of spherical dry particles to improve the flatness and density of the glaze surface.

Benefits of technology

The ultra-flat glaze surface of ceramic rock slabs is realized, the gloss and wear resistance of the glaze surface are improved, the corrosion resistance is enhanced, the flatness reaches within ±0.05mm, the gloss is 92-96GU, and the wear resistance level can reach level 5.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of architectural ceramics, and particularly discloses a super-flat glazed ceramic rock plate and a preparation method thereof. The ceramic rock plate sequentially comprises a green body, a ground glaze layer, a pattern layer, an isolation glaze layer and a cover glaze layer from bottom to top, raw material components of the isolation glaze layer comprise spherical dry particles and a first fluxing agent, the particle size of the spherical dry particles is 20-80 meshes, the particle size of the spherical dry particles is 35-75 meshes, and the initial melting point of the spherical dry particles is 900-950 DEG C; the raw material components of the cover glaze layer comprise irregular dry particles and a second fluxing agent, the particle sizes of the irregular dry particles comprise 120-230 meshes and 260-300 meshes, the initial melting point of the irregular dry particles is 850-900 DEG C, and the initial melting point of the irregular dry particles is lower than that of the spherical dry particles. According to the prepared ceramic rock plate, the flatness is within + / -0.05 mm, the glossiness is 92-96 GU, the wear-resistant level can reach the level 5, and the corrosion resistance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building ceramics, and specifically relates to an ultra-flat glazed ceramic rock slab and a preparation method thereof. Background Art

[0002] As a new type of building decoration material, ceramic rock slabs have been widely used in the field of building decoration because of their excellent properties, such as high strength, high hardness, high temperature resistance, corrosion resistance, etc. However, there are still some shortcomings in the existing ceramic rock slab production technology. For example, it is often difficult to obtain an ultra-flat glaze effect during the preparation process of existing ceramic rock slabs. This is due to the limitations of the glaze formula and preparation process, which makes the glaze surface prone to ripples and uneven defects, affecting the appearance quality and decorative effect of the ceramic rock slab. In addition, the existing technical methods also have certain limitations in improving the wear resistance and corrosion resistance of ceramic rock slabs, which makes ceramic rock slabs prone to wear, corrosion and other problems during use, reducing their service life and use value.

[0003] According to GB / T 3810.2-2016 "Test Methods for Ceramic Tiles - Part 2: Inspection of Dimensions and Surface Quality", the surface flatness standard for ordinary ceramic tiles is ±0.5mm. At present, there is no unified standard for super-flat glazed ceramic tiles in the industry. It is generally believed that super-flat glazed ceramic rock slabs refer to ceramic rock slabs with a surface flatness within ±0.05mm, which is much flatter than ordinary ceramic tiles and has a mirror-like smooth effect. Summary of the invention

[0004] The present invention proposes an ultra-flat glazed ceramic rock slab and a preparation method thereof to solve one or more technical problems existing in the prior art and at least provide a beneficial choice or create conditions.

[0005] In order to solve the above technical problems, the first aspect of the present invention provides a ceramic rock plate, which comprises, from bottom to top, a body, a bottom glaze layer, a pattern layer, an isolation glaze layer and a surface glaze layer;

[0006] The raw material components of the isolation glaze layer include spherical dry particles and a first flux, the particle size of the spherical dry particles includes 20-80 mesh and 35-75 mesh, and the initial melting point of the spherical dry particles is 900-950°C;

[0007] The raw material components of the surface glaze layer include irregular dry particles and a second flux, the irregular dry particles have particle sizes of 120-230 mesh and 260-300 mesh, the irregular dry particles have an initial melting point of 850-900° C., and the initial melting point of the irregular dry particles is lower than the initial melting point of the spherical dry particles.

[0008] Specifically, on the one hand, the present invention improves the smoothness of the glaze surface by controlling the particle size distribution and shape of the dry particles in the isolation glaze layer and the surface glaze layer. Among them: coarser spherical dry particles of different particle sizes are used in the isolation glaze layer, and the spherical dry particles can better arrange and fill the space in the glaze layer, which is conducive to forming a uniform glaze surface structure; in addition, the distribution of different particle sizes helps to improve the density and uniformity of the glaze surface. Finer irregular dry particles of different particle sizes are used in the surface glaze layer. Irregular dry particles refer to dry particles without specific regular geometric shapes, such as fragments, blocks, prisms, etc., which can be prepared by conventional water quenching methods. Spherical dry particles and irregular dry particles of various particle sizes fill each other to form a dense and uniform glaze surface structure, thereby improving the smoothness of the glaze surface.

[0009] On the other hand, the present invention controls the initial melting point of the spherical dry particles and the irregular dry particles within a certain range, and makes the initial melting point of the irregular dry particles lower than the initial melting point of the spherical dry particles, so as to further improve the flatness of the glaze surface and realize an ultra-flat glaze surface. Among them: the initial melting point of the spherical dry particles is relatively high (900-950°C), and they begin to melt later than the irregular dry particles during the firing process. This layered melting order is conducive to ensuring that the isolation glaze layer first forms a relatively stable structure, providing a good foundation for the melting and fusion of the subsequent surface glaze layer. When the firing temperature is increased to 850-900°C, the irregular dry particles begin to melt, and they can better fill and cover the structure that has been formed on the isolation glaze layer to form a more delicate and uniform glaze surface structure. Studies have found that the initial melting point of the irregular dry particles is too high, which can easily lead to a large amount of melting at the same time or too early with the spherical dry particles during the firing process, thereby causing excessive mixing and loss of glaze components, affecting the performance and quality of the glaze surface. By controlling the initial melting point at a lower level, the irregular dry particles can be gradually melted at a suitable temperature, maintaining the relative stability of the glaze composition and avoiding the decrease in glaze smoothness caused by uneven composition. In addition, controlling the initial melting point of spherical dry particles and irregular dry particles within a suitable range is also conducive to optimizing the chemical composition and structure of the glaze, improving the density of the glaze, and thus enhancing the wear resistance and corrosion resistance of the glaze.

[0010] In some embodiments of the present invention, the sphericity of the spherical dry particles is 0.9-1.0. A high sphericity is more conducive to the filling of the spherical dry particles, thereby forming a uniform glaze structure.

[0011] In some embodiments of the present invention, the bulk density of the spherical dry particles is 1.5-2.0 g / cm 3 The appropriate density enables it to maintain good suspension in the glaze and effectively fill the space during the firing process to avoid hollow or loose structures.

[0012] In some embodiments of the present invention, in the spherical dry particles, the mass ratio of 20-80 mesh spherical dry particles to 35-75 mesh spherical dry particles is (1-3):1.

[0013] In some embodiments of the present invention, the chemical composition of the spherical dry particles includes, by weight percentage: SiO2 45-56%, Al2O3 9-12%, TiO2 0.03-0.18%, CaO 12-14%, MgO1-2%, K2O 3-7%, Na2O3-7%, ZnO 6-10%, BaO 1-4%, ZrO2 0.05-0.8%, P2O5 0.03-0.08%, and loss on ignition 0.6-0.9%.

[0014] Specifically, the chemical composition of the spherical dry particles mainly includes SiO2, Al2O3 and CaO, and contains a small amount of ZnO, BaO and MgO, which give the spherical dry particles good physical and chemical properties. Among them: SiO2, as a network former, constitutes the basic skeleton structure of the glaze, which is beneficial to improve the hardness and stability of the glaze. Al2O3 can enter the network structure of SiO2 in the glaze structure to form an aluminum-silicon-oxygen network, which is more stable than the silicon-oxygen network because Al 3+ The ionic radius is larger than that of Si 4+ Slightly larger, Al 3 + The introduction of CaO causes a certain distortion in the network structure, thereby increasing the complexity and stability of the structure. In the multi-layer structure of the ceramic rock plate, this stable aluminum-silicon-oxygen network structure runs through the base glaze layer and the surface glaze layer, enhancing the bonding force between the layers and also improving the overall wear resistance of the glaze. As a flux, CaO can make the glaze melt and flow at a lower temperature, filling between other components to form a dense structure, further improving the wear resistance of the glaze.

[0015] In some embodiments of the present invention, the raw material components of the first flux include, by weight: 40-65 parts of glass powder, 2-6 parts of soda ash, 2-6 parts of lithium carbonate, 3-7 parts of calcium fluoride, 1-5 parts of magnesite powder, 1-5 parts of strontium oxide, and 1-5 parts of barium oxide.

[0016] Specifically, the first flux helps to lower the melting point of the spherical dry particles and promote their melting and fusion during the firing process. Among them: glass powder can form a stable glass phase structure during the firing process and fill in the gaps in the glaze layer, reducing the channels for external corrosive substances to enter the glaze layer, thereby improving the corrosion resistance of the glaze surface. Alkali metal compounds such as soda ash and lithium carbonate are beneficial to adjust the pH value of the glaze, making it in a relatively stable chemical environment, which is not conducive to the chemical reaction of corrosive substances, thereby enhancing the corrosion resistance of the glaze surface. Calcium fluoride, dolomite powder, strontium oxide, barium oxide and other ingredients can react chemically with other ingredients in the glaze layer to form stable compounds, and cover the surface of the glaze layer or fill in the interior of the glaze layer to prevent the erosion of corrosive substances.

[0017] In some embodiments of the present invention, the mass ratio of the spherical dry particles to the first flux is (1.5-4):1. The spherical dry particles and the first flux cooperate with each other so that the isolation glaze layer can form a uniform glaze structure during the firing process, thereby improving the flatness of the glaze surface.

[0018] In some embodiments of the present invention, among the irregular dry particles, the mass ratio of the irregular dry particles of 120-230 mesh to the irregular dry particles of 260-300 mesh is (1-3):1.

[0019] In some embodiments of the present invention, the chemical composition of the irregular dry particles is the same as that of the spherical dry particles. The spherical dry particles and irregular dry particles with the same chemical composition but different particle sizes and shapes have good compatibility. At the same time, SiO2 in the surface glaze layer is conducive to further strengthening the hardness of the surface and improving the wear resistance of the glaze.

[0020] In some embodiments of the present invention, the raw material components of the second flux include, by weight: 20-45 parts of glass powder, 2-6 parts of soda ash, 1-3 parts of lithium carbonate, 1-4 parts of calcium fluoride, 1-5 parts of magnesite powder, 1-7 parts of strontium oxide, and 1-3 parts of barium oxide.

[0021] Specifically, the second flux has similar raw material components to the first flux, and while promoting sintering, it is also beneficial to improving the chemical stability and corrosion resistance of the glaze.

[0022] In some embodiments of the present invention, the mass ratio of the irregular dry particles to the second flux is (0.2-0.7):1.

[0023] In some embodiments of the present invention, the thermal expansion coefficient of the isolation glaze layer is between the base glaze layer and the surface glaze layer, and the thermal expansion coefficient of the isolation glaze layer is 5×10 -6 -8×10 -6 / ℃.

[0024] Specifically, the present invention controls the composition and amount of the spherical dry particles and the first flux in the isolation glaze layer to regulate the thermal expansion coefficient of the isolation glaze layer so that it is between the base glaze layer and the surface glaze layer, thereby improving the adaptability and stability of the entire ceramic rock slab in different temperature environments.

[0025] In some embodiments of the present invention, the raw material components of the base glaze layer include, by weight: 50-55 parts of feldspar, 12-20 parts of cordierite, 4-6 parts of calcined zinc oxide, 7-10 parts of kaolin, 2-6 parts of dolomite, 5-10 parts of talc, 5-7 parts of alumina, and 2-5 parts of montmorillonite.

[0026] Specifically, the base glaze layer can better bond with the surface of the rock slab body during the firing process, while providing a flat and stable attachment basis for the isolation glaze layer and the surface glaze layer, further improving the flatness of the product.

[0027] In some embodiments of the present invention, the raw material components of the blank include, by weight: 45-50 parts of water-abrasive, 4-6 parts of wollastonite, 2-5 parts of raw talc, 1-3 parts of calcined talc, 7-9 parts of feldspar, 2-3 parts of kaolin, 20-30 parts of washed ball clay, and 5-10 parts of bentonite. The raw material components of the water-abrasive include, by weight: 45-55 parts of potassium feldspar, 35-45 parts of sodium feldspar, and 8-12 parts of mica.

[0028] The second aspect of the present invention provides a method for preparing the above-mentioned ceramic rock plate, comprising the following steps:

[0029] Wet-mixing the spherical dry particles and the first flux to obtain an isolation glaze slurry;

[0030] dry-mixing the irregular dry particles with a second flux to obtain a surface glaze;

[0031] The base glaze, inkjet-printed pattern, and the insulating glaze slurry are applied on the surface of the blank in sequence, and then the surface glaze is applied by dry method, and shaping glue is sprayed to form the base glaze layer, pattern layer, insulating glaze layer and surface glaze layer in sequence, and the ceramic rock slab is obtained after drying and firing.

[0032] In some embodiments of the present invention, the shaping glue is an aqueous solution of carboxymethyl cellulose.

[0033] In some embodiments of the present invention, the mass concentration of the aqueous solution of carboxymethyl cellulose is 1-1.2%.

[0034] In some embodiments of the present invention, the maximum sintering temperature is 1150-1200° C., and the holding time at the maximum temperature is 10-20 min.

[0035] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:

[0036] (1) The ceramic rock slab of the present invention comprises a base glaze layer, an isolation glaze layer and a surface glaze layer. On the one hand, the particle size distribution and shape of the dry particles in the isolation glaze layer and the surface glaze layer are controlled to improve the flatness of the glaze surface. On the other hand, the initial melting point of the spherical dry particles and the irregular dry particles is controlled within a certain range, and the initial melting point of the irregular dry particles is made lower than the initial melting point of the spherical dry particles, so as to further improve the flatness and density of the glaze surface and realize an ultra-flat glaze surface, thereby effectively overcoming the technical problem in the prior art that the glaze surface is prone to ripples and uneven defects, and enhancing the wear resistance and corrosion resistance of the glaze surface.

[0037] (2) The ceramic rock slab prepared by the present invention has a flatness within ±0.05 mm, a glossiness of 92-96 GU, a wear resistance level of up to level 5, and excellent corrosion resistance. DETAILED DESCRIPTION

[0038] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.

[0039] The raw material components of the blanks used in the following examples and comparative examples include, by weight: 48 parts of water-abrasive, 5 parts of wollastonite, 3 parts of raw talc, 2 parts of calcined talc, 8 parts of feldspar, 2.5 parts of kaolin, 25 parts of washed ball clay, and 6.5 parts of bentonite. Among them: the raw material components of the water-abrasive include, by weight: 50 parts of potassium feldspar, 40 parts of sodium feldspar, and 10 parts of mica.

[0040] Example 1

[0041] A ceramic rock slab comprises, from bottom to top, a body, a base glaze layer, a pattern layer, an isolation glaze layer and a surface glaze layer.

[0042] The raw material components of the bottom glaze layer include, by weight: 52 parts of feldspar, 16 parts of cordierite, 5 parts of calcined zinc oxide, 8 parts of kaolin, 4 parts of dolomite, 7 parts of talc, 6 parts of alumina, and 4 parts of montmorillonite; the thermal expansion coefficient of the bottom glaze layer is 4.8×10 -6 / ℃.

[0043] The raw material components of the isolation glaze layer include spherical dry particles and a first flux in a mass ratio of 2:1, wherein the spherical dry particles include 20-80 mesh spherical dry particles and 35-75 mesh spherical dry particles in a mass ratio of 1:1, and the initial melting point of the spherical dry particles is 925°C. The chemical composition of the spherical dry particles includes, by weight percentage: SiO2 53.8%, Al2O3 11%, TiO2 0.1%, CaO 13%, MgO 2%, K2O 5%, Na2O 2.4%, ZnO 9%, BaO 3%, ZrO2 0.65%, P2O5 0.05%, and ignition loss 0.8%. The raw material components of the first flux include, by weight: 53 parts of glass powder, 4 parts of soda ash, 4 parts of lithium carbonate, 5 parts of calcium fluoride, 3 parts of magnesite powder, 3 parts of strontium oxide, and 3 parts of barium oxide; the thermal expansion coefficient of the isolation glaze layer is 5×10 -6 / ℃.

[0044] The raw material components of the surface glaze layer include irregular dry particles and a second flux in a mass ratio of 0.4:1, wherein the irregular dry particles include irregular dry particles of 120-230 mesh and irregular dry particles of 260-300 mesh in a mass ratio of 1:1, and the irregular dry particles have an initial melting point of 875°C, and the chemical composition of the irregular dry particles is the same as that of the spherical dry particles. The raw material components of the second flux include, by weight, 33 parts of glass powder, 4 parts of soda ash, 2 parts of lithium carbonate, 2 parts of calcium fluoride, 3 parts of magnesite powder, 4 parts of strontium oxide, and 2 parts of barium oxide; the thermal expansion coefficient of the surface glaze layer is 5.2×10 -6 / ℃.

[0045] A method for preparing a ceramic rock plate, characterized in that it comprises the following steps:

[0046] (1) weighing raw materials according to the raw material components of the green body, adding 0.3% of sodium tripolyphosphate and 0.2% of sodium carboxymethyl cellulose by weight of the total raw material, adding water (material-water ratio is 100:30) for ball milling, and obtaining a green body slurry with a fineness of 0.4wt% of 325 mesh residue; then spraying and granulating the green body slurry to obtain a green body powder; and then aging the green body powder, pressing and forming, and drying to obtain a green body;

[0047] (2) weighing raw materials according to the raw material components of the base glaze layer, adding 0.3% of the total weight of sodium tripolyphosphate and 0.3% of sodium carboxymethyl cellulose, adding water (material-water ratio is 100:30) for ball milling, passing through a 100-mesh sieve to obtain a base glaze slurry; then pouring the glaze on the surface of the body with a bell jar, the glaze thickness is 0.5 mm, to form a base glaze layer;

[0048] (3) Inkjet print the pattern on the surface of the base glaze layer, and control the ink volume to 8g / cm during printing. 2 , get the pattern layer;

[0049] (4) Weighing spherical dry particles and a first flux according to the raw material components of the isolation glaze layer, then adding 0.3% of the total weight of sodium tripolyphosphate and 0.2% of sodium carboxymethyl cellulose to the first flux raw material, adding water (material-water ratio of 100:30) for ball milling, and obtaining a first flux slurry with a fineness of 0.4wt% of the residue on a 325-mesh sieve; then adding spherical dry particles to the first flux slurry, mixing evenly, to obtain an isolation glaze slurry; and then applying the isolation glaze slurry on the pattern layer by a spray gun, controlling the spraying pressure to 0.3MPa, the flow rate to 30mL / s, and the spraying thickness to 0.3mm, to form an isolation glaze layer;

[0050] (5) The irregular dry particles and the second flux are mixed uniformly according to the mass ratio to obtain a glaze; the glaze is applied by dry method at a rate of 120 g / m 2 Spread the amount on the isolation glaze layer, spray a 1.1% carboxymethyl cellulose aqueous solution as the setting glue, and the spraying amount is 20mL / m 2 , so that the surface glaze is bonded and fixed to form a surface glaze layer with a thickness of 0.4mm; after drying, it is put into the kiln for firing, the highest firing temperature is 1180℃, and the insulation time of the highest firing temperature is 15min, to obtain a ceramic rock plate; finally, use a grinding equipment to grind the surface of the surface glaze layer at a rotation speed of 1000 rpm to obtain the ceramic rock plate of this embodiment.

[0051] Example 2

[0052] A ceramic rock slab comprises, from bottom to top, a body, a base glaze layer, a pattern layer, an isolation glaze layer and a surface glaze layer.

[0053] The raw material components of the bottom glaze layer include, by weight: 53 parts of feldspar, 16 parts of cordierite, 5 parts of calcined zinc oxide, 8 parts of kaolin, 4 parts of dolomite, 7 parts of talc, 6 parts of aluminum oxide, and 4 parts of montmorillonite; the thermal expansion coefficient of the bottom glaze layer is 4.8×10 -6 / ℃.

[0054] The raw material components of the isolation glaze layer include spherical dry particles and a first flux in a mass ratio of 2:1, wherein the spherical dry particles include 30-mesh spherical dry particles and 65-mesh spherical dry particles in a mass ratio of 3:1, and the initial melting point of the spherical dry particles is 935°C. The chemical composition of the spherical dry particles includes, by weight percentage: SiO2 54.7%, Al2O3 10%, TiO2 0.1%, CaO13%, MgO 1%, K2O 5%, Na2O 5%, ZnO 8%, BaO 2%, ZrO2 0.4%, P2O5 0.05%, and ignition loss 0.75%. The raw material components of the first flux include, by weight: 40 parts of glass powder, 5 parts of soda ash, 4 parts of lithium carbonate, 6 parts of calcium fluoride, 3 parts of magnesite powder, 2 parts of strontium oxide, and 2 parts of barium oxide; the thermal expansion coefficient of the isolation glaze layer is 5×10-6 / ℃.

[0055] The raw material components of the surface glaze layer include irregular dry particles and a second flux in a mass ratio of 0.7:1, wherein the irregular dry particles include 120-mesh irregular dry particles and 300-mesh irregular dry particles in a mass ratio of 1:1, and the irregular dry particles have an initial melting point of 890°C, and the chemical composition of the irregular dry particles is the same as that of the spherical dry particles. The raw material components of the second flux include, by weight, 33 parts of glass powder, 4 parts of soda ash, 2 parts of lithium carbonate, 2 parts of calcium fluoride, 3 parts of magnesite powder, 4 parts of strontium oxide, and 2 parts of barium oxide; the thermal expansion coefficient of the surface glaze layer is 5.2×10 -6 / ℃.

[0056] A method for preparing a ceramic rock plate, characterized in that it comprises the following steps:

[0057] (1) weighing raw materials according to the raw material components of the green body, adding 0.3% of sodium tripolyphosphate and 0.2% of sodium carboxymethyl cellulose by weight of the total raw material, adding water (material-water ratio is 100:30) for ball milling, and obtaining a green body slurry with a fineness of 0.4wt% of 325 mesh residue; then spraying and granulating the green body slurry to obtain a green body powder; and then aging the green body powder, pressing and forming, and drying to obtain a green body;

[0058] (2) weighing raw materials according to the raw material components of the base glaze layer, adding 0.3% of the total weight of sodium tripolyphosphate and 0.3% of sodium carboxymethyl cellulose, adding water (material-water ratio is 100:30) for ball milling, passing through a 100-mesh sieve to obtain a base glaze slurry; then pouring the glaze on the surface of the body with a bell jar, the glaze thickness is 0.5 mm, to form a base glaze layer;

[0059] (3) Inkjet print the pattern on the surface of the base glaze layer, and control the ink volume to 8g / cm during printing. 2 , get the pattern layer;

[0060] (4) Weighing spherical dry particles and a first flux according to the raw material components of the isolation glaze layer, then adding 0.3% of the total weight of sodium tripolyphosphate and 0.2% of sodium carboxymethyl cellulose to the first flux raw material, adding water (material-water ratio of 100:30) for ball milling, and obtaining a first flux slurry with a fineness of 0.4wt% of the residue on a 325-mesh sieve; then adding spherical dry particles to the first flux slurry, mixing evenly, to obtain an isolation glaze slurry; and then applying the isolation glaze slurry on the pattern layer by a spray gun, controlling the spraying pressure to 0.3MPa, the flow rate to 30mL / s, and the spraying thickness to 0.3mm, to form an isolation glaze layer;

[0061] (5) The irregular dry particles and the second flux are mixed uniformly according to the mass ratio to obtain a glaze; the glaze is applied by dry method at a rate of 120 g / m 2Spread the amount on the isolation glaze layer, spray a 1.1% carboxymethyl cellulose aqueous solution as the setting glue, and the spraying amount is 20mL / m 2 , so that the surface glaze is bonded and fixed to form a surface glaze layer with a thickness of 0.4mm; after drying, it is put into the kiln for firing, the maximum firing temperature is 1200℃, and the insulation time of the maximum firing temperature is 15min, to obtain a ceramic rock plate; finally, use a grinding equipment to grind the surface of the surface glaze layer at a rotation speed of 1000 rpm to obtain the ceramic rock plate of this embodiment.

[0062] Example 3

[0063] A ceramic rock slab comprises, from bottom to top, a body, a base glaze layer, a pattern layer, an isolation glaze layer and a surface glaze layer.

[0064] The raw material components of the bottom glaze layer include, by weight: 53 parts of feldspar, 16 parts of cordierite, 5 parts of calcined zinc oxide, 8 parts of kaolin, 4 parts of dolomite, 7 parts of talc, 6 parts of alumina, and 4 parts of montmorillonite; the thermal expansion coefficient of the bottom glaze layer is 6.5×10 -6 / ℃.

[0065] The raw material components of the isolation glaze layer include spherical dry particles and a first flux in a mass ratio of 3:1, wherein the spherical dry particles include 20-80 mesh spherical dry particles and 35-75 mesh spherical dry particles in a mass ratio of 2.5:1, and the initial melting point of the spherical dry particles is 920°C. The chemical composition of the spherical dry particles includes, by weight percentage: SiO2 54.2%, Al2O3 10%, TiO20.1%, CaO 13%, MgO 1.5%, K2O 5%, Na2O 5%, ZnO 8%, BaO 2%, ZrO2 0.4%, P2O50.05%, and ignition loss 0.75%. The raw material components of the first flux include, by weight: 53 parts of glass powder, 4 parts of soda ash, 4 parts of lithium carbonate, 5 parts of calcium fluoride, 3 parts of magnesite powder, 3 parts of strontium oxide, and 3 parts of barium oxide; the thermal expansion coefficient of the isolation glaze layer is 7×10 -6 / ℃.

[0066] The raw material components of the surface glaze layer include irregular dry particles and a second flux at a mass ratio of 0.6:1, wherein the irregular dry particles include irregular dry particles of 180 mesh and irregular dry particles of 260 mesh at a mass ratio of 2:1, and the irregular dry particles have an initial melting point of 900°C, and the chemical composition of the irregular dry particles is the same as that of the spherical dry particles. The raw material components of the second flux include, by weight, 33 parts of glass powder, 4 parts of soda ash, 2 parts of lithium carbonate, 2 parts of calcium fluoride, 3 parts of magnesite powder, 4 parts of strontium oxide, and 2 parts of barium oxide; the thermal expansion coefficient of the surface glaze layer is 7.2×10 -6 / ℃.

[0067] A method for preparing a ceramic rock plate, characterized in that it comprises the following steps:

[0068] (1) weighing raw materials according to the raw material components of the green body, adding 0.3% of sodium tripolyphosphate and 0.2% of sodium carboxymethyl cellulose by weight of the total raw material, adding water (material-water ratio is 100:30) for ball milling, and obtaining a green body slurry with a fineness of 0.4wt% of 325 mesh residue; then spraying and granulating the green body slurry to obtain a green body powder; and then aging the green body powder, pressing and forming, and drying to obtain a green body;

[0069] (2) weighing raw materials according to the raw material components of the base glaze layer, adding 0.3% of the total weight of sodium tripolyphosphate and 0.3% of sodium carboxymethyl cellulose, adding water (material-water ratio is 100:30) for ball milling, passing through a 100-mesh sieve to obtain a base glaze slurry; then pouring the glaze on the surface of the body with a bell jar, the glaze thickness is 0.5 mm, to form a base glaze layer;

[0070] (3) Inkjet print the pattern on the surface of the base glaze layer, and control the ink volume to 8g / cm during printing. 2 , get the pattern layer;

[0071] (4) Weighing spherical dry particles and a first flux according to the raw material components of the isolation glaze layer, then adding 0.3% of the total weight of sodium tripolyphosphate and 0.2% of sodium carboxymethyl cellulose to the first flux raw material, adding water (material-water ratio of 100:30) for ball milling, and obtaining a first flux slurry with a fineness of 0.4wt% of the residue on a 325-mesh sieve; then adding spherical dry particles to the first flux slurry, mixing evenly, to obtain an isolation glaze slurry; and then applying the isolation glaze slurry on the pattern layer by a spray gun, controlling the spraying pressure to 0.3MPa, the flow rate to 30mL / s, and the spraying thickness to 0.3mm, to form an isolation glaze layer;

[0072] (5) The irregular dry particles and the second flux are mixed uniformly according to the mass ratio to obtain a glaze; the glaze is applied by dry method at a rate of 120 g / m 2 Spread the amount on the isolation glaze layer, spray a 1.1% carboxymethyl cellulose aqueous solution as the setting glue, and the spraying amount is 20mL / m 2 , so that the surface glaze is bonded and fixed to form a surface glaze layer with a thickness of 0.4mm; after drying, it is put into the kiln for firing, the maximum firing temperature is 1150℃, and the insulation time of the maximum firing temperature is 20min, to obtain a ceramic rock plate; finally, use a grinding equipment to grind the surface of the surface glaze layer at a rotation speed of 1000 rpm to obtain the ceramic rock plate of this embodiment.

[0073] Comparative Example 1

[0074] The only difference between Comparative Example 1 and Example 1 is that 40-60 mesh spherical dry particles are used in the isolation glaze layer of the ceramic rock board in Comparative Example 1.

[0075] Comparative Example 2

[0076] The only difference between Comparative Example 2 and Example 1 is that spherical dry particles are used in the glaze layer of the ceramic rock plate of Comparative Example 2 to replace the irregular dry particles in Example 1, and the particle size of the replaced spherical dry particles is the same as that of Example 1.

[0077] Comparative Example 3

[0078] The only difference between Comparative Example 3 and Example 1 is that the initial melting point of the irregular dry particles in the surface glaze layer of the ceramic rock board of Comparative Example 3 is the same as the chemical composition of the spherical dry particles in the isolation glaze layer, and the initial melting point is 925°C.

[0079] Comparative Example 4

[0080] The only difference between Comparative Example 4 and Example 1 is that the raw material components of the base glaze layer of the ceramic rock slab in Comparative Example 4 are different.

[0081] The raw material components of the base glaze layer of Comparative Example 4 include, by weight: 45 parts of feldspar, 10 parts of cordierite, 3 parts of calcined zinc oxide, 6 parts of kaolin, 3 parts of dolomite, 4 parts of talc, 4 parts of aluminum oxide, and 3 parts of montmorillonite.

[0082] Performance Testing

[0083] The ceramic rock plate samples prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-4 were tested for flatness, glossiness, wear resistance and corrosion resistance. The test standards are GB / T 3810.2-2016 "Test Methods for Ceramic Tiles - Part 2: Inspection of Dimensions and Surface Quality", GB / T 13891-2008 "Measurement Method for Specular Glossiness of Building Finishing Materials", GB / T 3810.7-2016 "Test Methods for Ceramic Tiles - Part 7: Determination of Surface Wear Resistance of Glazed Tiles", and the wear resistance is divided into 0-5 levels, with 0 indicating the worst wear resistance and 5 indicating the best wear resistance. The greater the number of revolutions of the same level, the better the wear resistance. GB / T 3810.13-2016 "Test Methods for Ceramic Tiles - Part 13: Determination of Chemical Corrosion Resistance". The test results are shown in Table 1.

[0084] Table 1:

[0085] sample Flatness(mm) Glossiness (GU) Wear resistance (grade) Corrosion resistance Example 1 ±0.05 92 5 excellent Example 2 ±0.05 96 5 excellent Example 3 ±0.05 94 5 excellent Comparative Example 1 ±0.10 69 4 good Comparative Example 2 ±0.08 76 3 middle Comparative Example 3 ±0.06 78 4 good Comparative Example 4 ±0.12 62 3 middle

[0086] It can be seen from Table 1 that the ceramic rock slabs prepared in Examples 1-3 have a flatness of ±0.05 mm and a glossiness of up to 92-96GU, with an ultra-flat glaze and high gloss; and the wear resistance level of the glaze can reach level 5, with excellent corrosion resistance.

[0087] Compared with Example 1, Comparative Examples 1-2 cannot achieve good filling and arrangement effects because spherical dry particles of a single particle size are used in the isolation glaze layer or spherical dry particles are used to replace irregular dry particles in the surface glaze layer, thereby affecting the density and flatness of the glaze surface, and further causing the gloss, wear resistance and corrosion resistance of the glaze surface to decrease.

[0088] Comparative Example 3 relative to Example 1, since the initial melting points of the isolation glaze layer and the surface glaze layer are the same, during the firing process, the irregular dry particles and the spherical dry particles melt in large quantities simultaneously or prematurely, causing excessive mixing and loss of glaze components, affecting the performance and quality of the glaze, causing a slight decrease in flatness, and at the same time, the glossiness, wear resistance and corrosion resistance are also reduced.

[0089] Compared with Example 1, in Comparative Example 4, since the base glaze layer adopts the base glaze of ordinary ceramic rock plate, the base glaze cannot provide a good adhesion basis, resulting in a significant decrease in the flatness of the surface glaze layer, and further a significant decrease in the glossiness, wear resistance and corrosion resistance of the glaze surface.

[0090] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.

Claims

1. A ceramic rock plate, characterized in that: From bottom to top, it includes the body, the bottom glaze layer, the pattern layer, the isolation glaze layer and the top glaze layer; The raw material components of the isolation glaze layer include spherical dry particles and a first flux, the particle size of the spherical dry particles includes 20-80 mesh and 35-75 mesh, and the initial melting point of the spherical dry particles is 900-950°C; The raw material components of the surface glaze layer include irregular dry particles and a second flux, the irregular dry particles have particle sizes of 120-230 mesh and 260-300 mesh, the irregular dry particles have an initial melting point of 850-900° C., and the initial melting point of the irregular dry particles is lower than the initial melting point of the spherical dry particles.

2. The ceramic rock plate according to claim 1, characterized in that: In the spherical dry particles, the mass ratio of 20-80 mesh spherical dry particles to 35-75 mesh spherical dry particles is (1-3):1; And / or, the chemical composition of the spherical dry particles includes, by weight percentage: SiO2 45-56%, Al2O3 9-12%, TiO2 0.03-0.18%, CaO 12-14%, MgO1-2%, K2O 3-7%, Na2O 3-7%, ZnO 6-10%, BaO 1-4%, ZrO2 0.05-0.8%, P2O5 0.03-0.08%, and loss on ignition 0.6-0.9%.

3. The ceramic rock plate according to claim 1 or 2, characterized in that: The raw material components of the first flux include, by weight: 40-65 parts of glass powder, 2-6 parts of soda ash, 2-6 parts of lithium carbonate, 3-7 parts of calcium fluoride, 1-5 parts of magnesite powder, 1-5 parts of strontium oxide, and 1-5 parts of barium oxide; And / or, the mass ratio of the spherical dry particles to the first flux is (1.5-4):

1.

4. The ceramic rock plate according to claim 2, characterized in that: In the irregular dry particles, the mass ratio of the irregular dry particles of 120-230 mesh to the irregular dry particles of 260-300 mesh is (1-3):1; And / or, the chemical composition of the irregular dry particles is the same as the chemical composition of the spherical dry particles.

5. The ceramic rock plate according to claim 1 or 4, characterized in that: The raw material components of the second flux include, by weight: 20-45 parts of glass powder, 2-6 parts of soda ash, 1-3 parts of lithium carbonate, 1-4 parts of calcium fluoride, 1-5 parts of magnesite powder, 1-7 parts of strontium oxide, and 1-3 parts of barium oxide; And / or, the mass ratio of the irregular dry particles to the second flux is (0.2-0.7):

1.

6. The ceramic rock plate according to claim 1, characterized in that: The thermal expansion coefficient of the isolation glaze layer is between the bottom glaze layer and the top glaze layer, and the thermal expansion coefficient of the isolation glaze layer is 5×10 -6 -8×10 -6 / ℃.

7. The ceramic rock plate according to claim 1, characterized in that: The raw material components of the base glaze layer include, by weight: 50-55 parts of feldspar, 12-20 parts of cordierite, 4-6 parts of calcined zinc oxide, 7-10 parts of kaolin, 2-6 parts of dolomite, 5-10 parts of talc, 5-7 parts of aluminum oxide, and 2-5 parts of montmorillonite.

8. A method for preparing a ceramic rock plate as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Wet mixing the spherical dry particles and the first flux to obtain an isolation glaze slurry; dry-mixing the irregular dry particles with a second flux to obtain a surface glaze; The base glaze, inkjet-printed pattern, and the insulating glaze slurry are applied on the surface of the blank in sequence, and then the surface glaze is applied by dry method, and shaping glue is sprayed to form the base glaze layer, pattern layer, insulating glaze layer and surface glaze layer in sequence, and the ceramic rock slab is obtained after drying and firing.

9. The method for preparing a ceramic rock plate according to claim 8, characterized in that: The shaping glue is an aqueous solution of carboxymethyl cellulose.

10. The method for preparing a ceramic rock plate according to claim 8, characterized in that: The maximum sintering temperature is 1150-1200° C., and the insulation time at the maximum temperature is 10-20 minutes.